Netamines O–S, Five New Tricyclic Guanidine Alkaloids from the Madagascar Sponge Biemna laboutei, and Their Antimalarial Activities. Issue 11 (November 2015) - Gros, Emmanuelle; Martin, Marie‐Thérèse; Sorres, Jonathan; Moriou, Céline; Vacelet, Jean; Frederich, Michel; Aknin, Maurice; Kashman, Yoel; Gauvin‐Bialecki, Anne; Al‐Mourabit, Ali
Abstract: In our continuing program to isolate new compounds from the Madagascar sponge Biemna laboutei, five new tricyclic guanidine alkaloids, netamines O – S (1 –5, resp.), have been identified together with the known compounds netamine E (6 ) and mirabilin J (7 ). The structures of all new netamines were assigned on the basis of spectroscopic analyses. Their relative configurations were established by analysis of ROESY data and comparison with literature data. Netamines O, P, and Q, which were isolated in sufficient quantities, were tested for their cytotoxic activities against KB cells and their activities against the malaria parasite Plasmodium falciparum. Netamines O and Q were found to be moderately cytotoxic. Netamines O, P, and Q exhibited antiplasmodial activities with IC 50 values of 16.99±4.12, 32.62±3.44, and 8.37±1.35 μM, respectively. Abstract :